International E-Government Development Policy, Implementation and Best Practice (Springer International Publishing, 2018)
This book provides an examination of e-government frameworks and maturity stages in governments around the world, including an overview of the legal frameworks that have supported them. Divided into three sections, the first part of this book analyses the theoretical context of current policies, codes of best practice and their implementation. The second section presents case studies which bring key issues to the fore including open government, privacy protection, social media, democracy, systems failures, innovations in inter-organizational e-government projects, and open data systems. The authors demonstrate the importance of the successful implementation of e-Government for improving managerial efficiency, public service delivery and citizen engagement, with special attention given to developing countries. The book concludes by drawing out the lessons learned from the latest research and recommending solutions for improving the implementation of e-Government in the future, thereby helping to achieve more transparent, participative and democratic societies. This book will provide an invaluable resource for researchers, policy-makers, public managers, international organizations and technical experts.